Ultrahigh Photoresponsivity of W/Graphene/β-Ga2O3 Schottky Barrier Deep Ultraviolet Photodiodes - Labed, Madani; Park, Bo-In; Kim, Jekyung; Park, Jang Hyeok; Min, Ji Young; Hwang, Hee Jae; Kim, Jeehwan; Rim, You Seung (American Chemical Society, 2024)
The integration of graphene with semiconductor materials has been studied for developing advanced electronic and optoelectronic devices. Here, we propose ultrahigh photoresponsivity of beta-Ga2O3 photodiodes with a graphene monolayer inserted in a W Schottky contact. After inserting the graphene monolayer, we found a reduction in the leakage current and ideality factor. The Schottky barrier height was also shown to be about 0.53 eV, which is close to an ideal value. This was attributed to a decrease in the interfacial state density and the strong suppression of metal Fermi-level pinning. Based on a W/graphene/beta-Ga2O3 structure, the responsivity and external quantum efficiency reached 14.49 A/W and 7044%, respectively. These values were over 100 times greater than those of the W contact alone. The rise and delay times of the W/graphene/beta-Ga2O3 Schottky barrier photodiodes significantly decreased to 139 and 200 ms, respectively, compared to those obtained without a graphene interlayer (2000 and 3000 ms). In addition, the W/graphene/beta-Ga2O3 Schottky barrier photodiode was highly stable, even at 150 degrees C.